Larra Wasps, Larra analis Fabricius; Mole Cricket Hunters, Larra bicolor Fabricius (suggested common names) (Insecta: Hymenoptera: Sphecidae) - John Howard Frank; Andrei Sourakov (EDIS)
This document is EENY-268, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: March 2002.